2015
DOI: 10.1007/s10765-015-1942-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gas Molecule Mean Free Path and Gaseous Thermal Conductivity in Confined Nanoporous Structures

Abstract: This study comprehensively analyzes the mean free path of gas molecules and gaseous thermal conductivity in confined nanoporous structures through a wide range of temperatures and pressures. A simplified unit cell cubic array structure of nanospheres is used to correlate microstructure features with specific surface area and density of nanoporous materials. Zeng's model is used to describe the mean free path of the gas molecules and the gaseous thermal conductivity in confined nanoporous structures, and experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
(58 reference statements)
1
6
0
Order By: Relevance
“…In our study, the thermal conductivity decreased with an increase in temperature. This temperature dependence is similar to that for crystalline materials because the thermal conductivity of amorphous materials increases with an increase in temperature in the room-temperature region [33][34][35][36]. Furthermore, B. Cui et al were carried out extensive thermal conductivity analysis of IGZO thin films at low temperature and reported that the result of thermal conductivity is varying widely depending on deposition technique such as physical layer deposition, sputtering, and chemical synthesis; deposition power, deposition temperature and structural phases such as amorphous, poly-crystal, and single crystal [37].…”
Section: Resultssupporting
confidence: 63%
“…In our study, the thermal conductivity decreased with an increase in temperature. This temperature dependence is similar to that for crystalline materials because the thermal conductivity of amorphous materials increases with an increase in temperature in the room-temperature region [33][34][35][36]. Furthermore, B. Cui et al were carried out extensive thermal conductivity analysis of IGZO thin films at low temperature and reported that the result of thermal conductivity is varying widely depending on deposition technique such as physical layer deposition, sputtering, and chemical synthesis; deposition power, deposition temperature and structural phases such as amorphous, poly-crystal, and single crystal [37].…”
Section: Resultssupporting
confidence: 63%
“…Moreover, SrTiO 3 , as a porous nanomaterial, can block a small amount of thermal radiation and reduce air convection. The larger specific surface area also increases the collision probability between the gas molecules and the interface, and the heat is dissipated during the transfer process, making the thermal conductivity smaller than that of the bulk material . The lower the thermal conductivity, the worse the heat conduction and the better the heat insulation effect .…”
Section: Resultsmentioning
confidence: 99%
“…The larger specific surface area also increases the collision probability between the gas molecules and the interface, and the heat is dissipated during the transfer process, making the thermal conductivity smaller than that of the bulk material. 22 The lower the thermal conductivity, the worse the heat conduction and the better the heat insulation effect. 23 In addition, dispersing CsPbBr 3 into SrTiO 3 at the nanoscale can also effectively inhibit the aggregation caused by the increasing temperature, thereby reducing the thermal quenching of CsPbBr 3 PQDs.…”
Section: Resultsmentioning
confidence: 99%
“…This result can be explained with the Knudsen number, K n , which is defined as the ratio of the mean free path ( λ¯) of the gas species to the pore diameter of the electrode . For hydrogen, the mean free path ( λH2¯) is ∼0.5 μm in the range from 600 to 1300 K . When the pore size is below ∼5 μm, K n is larger than 0.1, and the Knudsen diffusivity contributes dominantly to the total diffusivity .…”
Section: Resultsmentioning
confidence: 99%